2009
DOI: 10.1002/cjoc.200990169
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Group 6 Metal Carbonyl Complexes with Bis(pyrazol‐1‐yl)methanes Modified by the Vinyltin Groups

Abstract: Diphenyl(vinyl)stannylbis(3,5-dimethylpyrazol-1-yl)methane and diphenyl(vinyl)stannylbis(3,4,5-trimethylpyrazol-1-yl)methane have been synthesized by the reaction of bis(3,5-dimethylpyrazol-1-yl)methyl or bis(3,4,5trimethylpyrazol-1-yl)methyllithium with diphenyl(vinyl)tin iodide. Treatment of these bis(pyrazol-1-yl)methanes modified by the vinyltin groups with M(CO) 5 THF (M=Mo and W) in refluxing THF resulted in new heterobimetallic complexes R 3 SnCHPz 2 M(CO) 3 (R 3 Sn represents trivinyltin or diphenyl(vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The sulfur and pyrazolyl nitrogen atoms do not coordinate to the tin atom, possibly owing to the weak Lewis acidity of the tin atom in tetraalkyltin. Reaction of 5 with Mo(CO) 6 or W(CO) 5 THF in refluxing THF yielded Ph 3 SnCH(SPh)(3,5-Me 2 Pz) M(CO) 4 (M ¼ Mo (6) and W (7), respectively), with certain amount of complex 2 in the case of tungsten. No oxidative addition product of the SneC sp3 or SneC sp2 bond to the molybdenum(0) or tungsten (0) atom was obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sulfur and pyrazolyl nitrogen atoms do not coordinate to the tin atom, possibly owing to the weak Lewis acidity of the tin atom in tetraalkyltin. Reaction of 5 with Mo(CO) 6 or W(CO) 5 THF in refluxing THF yielded Ph 3 SnCH(SPh)(3,5-Me 2 Pz) M(CO) 4 (M ¼ Mo (6) and W (7), respectively), with certain amount of complex 2 in the case of tungsten. No oxidative addition product of the SneC sp3 or SneC sp2 bond to the molybdenum(0) or tungsten (0) atom was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Related reaction of 1-phenylthiomethyl-3,5-dimethylpyrazole 1-Phenylthiomethyl-3,5-dimethylpyrazole [PhSCH 2 (3,5-Me 2 Pz), Pz ¼ pyrazol-1-yl] has been synthesized for about two decades [9], but its coordination chemistry has drawn little attention. To gain more convictive knowledge on its coordination ability to transition metals and comprehensive foundations for further research, we started our investigations with the reaction of this ligand with M (CO) 6 (M ¼ Mo or W) (Scheme 1). Reaction of PhSCH 2 (3,5-Me 2 Pz) with Mo(CO) 6 produced PhSCH 2 (3,5-Me 2 Pz)Mo(CO) 4 (1), similar reaction with W(CO) 6 yielded analogous complex PhSCH 2 (3,5-Me 2 Pz)W(CO) 4 (2) and concomitant desulfurized complex (3,5-Me 2 PzH)W(CO) 5 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions of bis(3,5-dimethylpyrazol-1-yl)-methyllithium with 6-phenylfulvene 8 and 6,6-diphenylfulvene 9 yielded the mixture of 1-[2,2-bis (3,5- 10 Complexes 3 and 4 form two isomers in solution owing to the interconversion of one hydrogen atom of the cyclopentadienyl ring. Two sets of 1 H NMR and 13 C NMR signals are observed for complexes 3 and 4, respectively, which is consistent with the presence of two tautomers, similar to those in ligands 1 and 2.…”
Section: Thfmentioning
confidence: 99%
“…Our previous investigation showed that treatment of bis(pyrazol-1-yl)-methanes functionalized by the organic groups on the bridgehead carbon atom with W(CO) 5 THF resulted in unusual reactivity. [10][11][12] As an extension of our investigations on functionalized bis(pyrazol-1-yl)methanes, herein we report the reactivity of the hybrid heteroscorpionate/cyclopentadienyl ligands with W(CO) 5 THF, which affords κ 2 -(N,N) bidentate or κ 3 -(π,N,N) tridentate derivatives, significantly different from those reported for other monosubstituted cyclopentadienes.…”
Section: Introductionmentioning
confidence: 95%